Hubungan Model Pembelajaran Team Assisted Individualization Dengan Prestasi Belajar Ditinjau Dari Taksonomi Bloom - Setianingsih, Evi; , Idris Harta, M.A., Ph.D (2015)
The purpose of this study is to analysis and examine of influence of Team Assisted Individualization (TAI) and Expository learning model toward matematic learning achievement. This study type is quantitative experiment study. Population in this study are 200 students of 7th grade in the academic year of 2014/2015, sample of this study consist of two different classes, there are VII E as control class and VII F as experiment class. Sampling technique used is cluster random sampling. Method of data collection used is result test of mathematic learning and documentation method. Data analysis method used in this study is chi square test. From the study result, concluded that there is influence of Team Assisted Individualization and expository learning model toward learning achievement, with chi square of Team Assisted Individualization (TAI) result is 95.4767 and chi square of Expository result is 74.7925.